The major causes of research misconduct - Al-Has, Asilah; Fadzil, A. Rahman; Shazwan, M. Shamin; Yunas, N. Syaheera; Bathumalai, Prasana; Shogar, Ibrahim (Farabi Publishing House, 2021)
Researchers’ integrity is of the important roles as a responsible researcher as their main job scope is finding, presenting, and reporting new solutions for every aspect of life to the world. This integrity will receive serious damage because of misconduct acts among unethical researchers because of personal gains or fame. Research misconduct (RM) has been defined as fabrication, falsification, and plagiarism of scientific data along the process of completing the research objective. This study aims to discuss the type and cause of research misconduct and ways to overcome it. The causes of RM due to poor supervision, personal circumstances, inadequate training and competitive pressure. In order to overcome RM two parties are responsible which involve the researcher and administrative department. In addition, advanced technology applications i.e. Turnitin (Internet-based plagiarism detection) could help the administration to monitor the RM activities. Hence, the early awareness of RM would create quality research and responsible researchers in future and among the public.